2011
DOI: 10.1002/ptr.3599
|View full text |Cite
|
Sign up to set email alerts
|

Reversal Effects of Components from the Fruits of Illicium simonsii on Human Adriamycin‐resistant MCF‐7 and 5‐Fluorouracil‐resistant Bel7402 Cells

Abstract: Twenty-one compounds including seven characteristic sesquiterpene lactones were isolated from Illicium simonsii and screened in vitro for their potential to restore the sensitivity of Adriamycin (ADR) resistant breast cancer cells (MCF-7/ADR) and 5-fluorouracil-resistant hepatocellular carcinoma cells (Bel7402/5-FU) to ADR and 5-fluorouracil, respectively. These compounds were found to be non-toxic to a panel of tumour cell lines: human breast cancer cells (MCF-7), cervical cancer cells (HeLa), hepatic liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Compounds with lower polarity generally had stronger sensitizing ability to the Pgp overexpressed in adriamycin resistant breast cancer cells. On the other hand, higher hydrophilic compounds seemed to exhibit a stronger reversal effect to the MRP overexpressed in 5-fluorouracil-resistant hepatocellular carcinoma cells (119). It has been shown that miRNAs play a critical role in drug transport and MDR (120).…”
Section: Kim Et Al Reported That Resveratrol Enhanced Doxorubicinindmentioning
confidence: 98%
“…Compounds with lower polarity generally had stronger sensitizing ability to the Pgp overexpressed in adriamycin resistant breast cancer cells. On the other hand, higher hydrophilic compounds seemed to exhibit a stronger reversal effect to the MRP overexpressed in 5-fluorouracil-resistant hepatocellular carcinoma cells (119). It has been shown that miRNAs play a critical role in drug transport and MDR (120).…”
Section: Kim Et Al Reported That Resveratrol Enhanced Doxorubicinindmentioning
confidence: 98%
“…[ 35 ] Another 2 components (Zedoary and Oldenlandia diffusa) also exhibit potential anticancer effects and restore the sensitivity of MCF-7/ADR (doxorubicin-resistant MCF-7 breast cancer cells) and A549/Taxol cells, modulating the multidrug resistance phenotype and the function of P-glycoprotein in human breast cancer cells. [ 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…It can competitively inhibit the transport function of P-gp without interrupting ATP hydrolysis, and increase the intracellular accumulation of many anticancer drugs to overcome the P-gpmediated MDR (Wang and Sun, 2020). Indole alkaloids such as Reserpine ( 10), Indole-3-carbinol and indole-3-carbaldehyde can inhibit P-gp mediated efflux of drugs like doxorubicin, vincristine (Henrich et al, 2006;Wei et al, 2012). 3,4,5-trimethoxybenzyl leuconicine A (11), a derivative of leuconicine A, is a potent P-gp inhibitor as it decreases the dose of vincristine in a resistant cancer cell lines (Munagala et al, 2014).…”
Section: Alkaloidsmentioning
confidence: 99%